2021
DOI: 10.3390/nano11051132
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Surface Plasmon Coupling of Quantum Wells in Nitride-Based LEDs: A Review of the Recent Advances

Abstract: Surface plasmon (SP)-enhanced quantum-well (QW) LEDs have proved their potential in replacing conventional lighting devices for their high-performance capabilities in ultraviolet (UV), blue and green spectral ranges. The SP-enhanced QW-LEDs have applications in light emission enhancement, light polarization, color conversion, and speed modulation. The electric field of the plasmonic mode of a metal couples with the exciton energy of QWs in resonance results in efficiency enhancement to several folds. The stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…It has been found that SP enhancement is rather a combined effect of absorption, scattering, scattering-to-extinction ratio, and field enhancement [ 3 , 22 ]. SP enhancement in LEDs depends on many factors such as metal type, geometry and size distribution of NPs, QW period number, QW emission wavelength, and GaN thickness [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that SP enhancement is rather a combined effect of absorption, scattering, scattering-to-extinction ratio, and field enhancement [ 3 , 22 ]. SP enhancement in LEDs depends on many factors such as metal type, geometry and size distribution of NPs, QW period number, QW emission wavelength, and GaN thickness [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…QCSE is the band-structure tilt in QWs due to the strong built-in piezoelectric feld [48][49][50][51]. It leads to low optical transition energy and poor recombination efciency in QW-LEDs as the wave function overlap decreases under the infuence of this feld [25,[52][53][54][55][56][57]. Tis built-in feld however plays a central role in terahertz generation upon ultrafast excitation of InGaN/ GaN QWs [33].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the weak hole injection and serious electron leakage in III-nitride LEDs are frequently mentioned and are believed that may play essential roles in their efficiency droop. [4][5][6][7] It is well known that the holes in III-nitride materials have a larger effective mass and smaller mobility than that of the electrons. In addition, Mg as an acceptor in III-nitride materials has a high ionization activation energy, which limits the effective hole concentration in p-GaN.…”
mentioning
confidence: 99%